Relativisme Budaya Dalam Penerapan HAM di Iran Analisis Kewajiban Berhijab - Annisa Eka Nurfitria (Neolectura, 2022)
Human rights are natural rights given by God for every human being. However, the difference in views between Islam and the West makes countries in the world have their own standards regarding human rights. If Western human rights make people the center of human rights, it is different from Islamic countries. They focused human rights on God, where God had absolute authority over man. The principle held by Islamic countries is supported by the opinion that human rights are flexible in nature depending on the culture, religion, and traditions of these countries. As a counterpoint to the Universal Declaration of Human Rights, Islamic countries formed a coalition to draft an Islamic version of the human rights declaration. And one of the countries that contributed to the drafting of the declaration was Iran. Iran after the revolution led by Ayatullah Khomeini in 1979, turned into the state of the Islamic Republic. They made Wilayatul Fakih a government system. Iran's constitution and laws are adopted from Islamic principles and laws, including the human rights values they hold. The results showed that human rights values such as natural rights, individual freedoms are always political if they are exposed to religious values, especially Islam. Because human rights values are indirectly taken from western values that are Christian in style. As for Islamic countries, which make religious foundations a constitution, human rights values are always supported by local culture. This research uses qualitative research, where the description requirements, whose research results contain synthesis and abstraction conclusions.